Assessing spatial and environmental drivers of phylogenetic structure in Brazilian Araucaria forests - Duarte, Leandro D. S.; Prieto, Pablo V.; Pillar, Valério D. (Ecography (Copenhagen), 2012)
Evidence of phylogenetic conservatism in plant ecological traits has accumulated over the past few years, suggesting an interplay between the distribution of phylogenetic clades and major environmental gradients. Nonetheless, determining what environmental factors underlie the distribution of phylogenetic lineages remains a challenge because environmental factors are correlated with spatial gradients where the latter might indicate some degree of dispersal limitation in phylogenetic pools. We analyzed the phylogenetic structure of plant assemblages across the Brazilian Araucaria forests and assessed how phylogenetic structure responds to environmental and spatial gradients. We compiled data on plant occurrence in 45 plots across the Araucaria forest biome. The phylogenetic structure of the plots was characterized using phylogenetic fuzzy-weighting followed by principal coordinates of phylogenetic structure (PCPS). We used distance-based redundancy analysis (db-RDA) to analyze the relationships between phylogenetic clades and environmental and spatial factors. Variation partitioning showed that the phylogenetic structure of Brazilian Araucaria forests was better explained by environment factors (altitude and annual mean temperature) than by space. Yet, spatially-structured environmental variation explained about one-third of total variation in the phylogenetic structure. Thus, the influence of spatial filters on the phylogenetic structure was more related to environmental gradients across the Brazilian Araucaria forest biome than to dispersal limitation of phylogenetic lineages. Furthermore, the influence of explanatory factors on the phylogenetic structure was concentrated in few nodes, the one splitting tree ferns from seed plants, and a second splitting malvids from other eurosids. Assessing the functional links between species distribution patterns and environmental gradients is not an easy task when we have to deal with large species pools. Identifying major phylogenetic gradients across an environmental and/or geographical range of interest can represent a first step towards a better understanding of general assembly processes in ecological communities.